Dermatofibrosarcoma protuberans of the anterior abdominal wall: case report and literature review. Issue 6 (30th June 2022) - Souiki, Tarik; Belhaj, Anas; Ait Abderrhim, Abderrahim; Alami, Badreeddine; Tahiri, Layla; Chbani, Laila; Ibn Majdoub, Karim; Toughrai, Imane; Mazaz, Khalid
Abstract: Dermatofibrosarcoma protuberans (DFSP) is a rare and slowly growing cutaneous tumor with high risk of local invasion and recurrence. Here, we report a case of a DFSP of the anterior abdominal wall diagnosed in a 45-year-old woman. The clinical examination showed an indurated well-limited oval mass localized in the supra-umbilical level and measuring 5 cm by 3 cm. The histological finding of skin biopsy was consistent with the diagnosis of DFSP. A wide local excision was performed while respecting minimum safety margins of 3 cm. The primary closure was possible after advancing the subcutaneous adjacent tissue. The histological examination of the surgical specimen confirmed the DFSP diagnosis and determined safe microscopic margins. After 4 years of regular follow-up, no locoregional or distant recurrence was observed. We discuss through this case the diagnosis difficulties and the particularities of the abdominal wall localization.